Peran Financial Technology (Fintech) Syariah dalam Meningkatkan Inklusi Keuangan di Indonesia: Analisis Perspektif Ekonomi Islam - Supriadi, Edi (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2024)
Amidst the development of digital technology, Sharia Financial Technology (Fintech) has emerged as an alternative solution that not only offers service efficiency but also ensures compliance with Islamic economic principles such as the prohibition of usury, distributive justice, and transaction ethics. This study aims to determine: (1) the concept of financial inclusion in conventional and Islamic economics; (2) the development and characteristics of Sharia Fintech in Indonesia; (3) Islamic economic principles such as maqashid al-shariah, distributive justice, and transaction ethics; and (4) policies and regulations that affect the Sharia Fintech ecosystem. The method used is a literature study with thematic analysis of academic literature and related regulations. The results show that Sharia Fintech has great potential in expanding fair and halal financial access, especially for groups of people who are not yet served by the conventional financial system. By integrating digital technology and Islamic values, Sharia Fintech is able to bridge the economic gap while strengthening Sharia financial literacy. However, challenges such as low public understanding of Sharia contracts and suboptimal specific regulations still need to be addressed. The implications of this study emphasize the importance of synergy between regulators, industry players, academics, and the community in building an inclusive, ethical, and sustainable Sharia Fintech ecosystem. This study also contributes theoretically to the development of a value-based financial inclusion model and provides a basis for formulating policies that are more responsive to the economic needs of the community.